2022
DOI: 10.3390/nu14112207
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Isolated Sarcopenia or Malnutrition–Sarcopenia Syndrome for Clinical Outcomes in Hospitalized Patients

Abstract: Malnutrition–sarcopenia syndrome (MSS) is frequent in the hospital setting. However, data on the predictive validity of sarcopenia and MSS are scarce. We evaluated the association between sarcopenia and MSS and clinical adverse outcomes (prolonged length of hospital stay—LOS, six-month readmission, and death) using a prospective cohort study involving adult hospitalized patients (n = 550, 55.3 ± 14.9 years, 53.1% males). Sarcopenia was diagnosed according to the EWGSOP2, and malnutrition according to the Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Malnutrition and sarcopenia overlap was found in 15.9% of patients in the current study. Malnutrition and sarcopenia share characteristics in common, leading to the suggestion of the existence of malnutrition‐sarcopenia syndrome (MSS) by Vandewoude et al 29 The presence of MSS has been associated with a fourfold increase in the chance of mortality in hospitalized older adult patients as analyzed by Hu et al 30 Sousa et al also found an association between MSS and longer hospital stays, hospital readmissions, and mortality in hospitalized patients 13 . However, it has been scarcely explored in outpatients with HF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malnutrition and sarcopenia overlap was found in 15.9% of patients in the current study. Malnutrition and sarcopenia share characteristics in common, leading to the suggestion of the existence of malnutrition‐sarcopenia syndrome (MSS) by Vandewoude et al 29 The presence of MSS has been associated with a fourfold increase in the chance of mortality in hospitalized older adult patients as analyzed by Hu et al 30 Sousa et al also found an association between MSS and longer hospital stays, hospital readmissions, and mortality in hospitalized patients 13 . However, it has been scarcely explored in outpatients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…11 The presence of malnutrition combined with sarcopenia has already been demonstrated to be associated with a poor prognosis in older adults 12 and in general hospitalized patients. 13 The prognostic value of malnutrition 5 and sarcopenia 14 diagnosis in patients with HF is well recognized, and poor quality of life is related to these diagnoses. However, we did not identify studies investigating whether the combination of both conditions are more deleterious for this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with other research that found a connection between MSS and extended duration of stay and readmission. For instance, MSS was discovered in research by Sousa et al [35] to be a predictor of worse outcomes in hospitalized patients. A deterioration in nutritional status during the rst week of hospitalization was linked to a higher risk of an extended duration of stay and readmission, according to impactful research by Correia et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, proteolysis leads the negative nitrogen balance. When this catabolic phase is severe, many patients tend to have a poor prognosis [3][4][5][6][7][8][9] . This trend applies to critically ill and neurological critically ill pa-tients 10) .…”
Section: Introductionmentioning
confidence: 99%